ECONOMIC OPTIMIZATION IN THE AGE OF ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES - Loso Judijanto; Melyana R Pugu; Anggi Setya Prayoga; Mohd Syahrin (Adisam Publisher, 2024)
The era of artificial intelligence (AI) arrived with promises of major transformation in various economic sectors. With its ability to automate routine tasks, improve decision-making, and enhance product and service innovation, AI has the potential to significantly improve operational efficiency and drive economic growth. The research methods carried out on this study are literature by searching for references that match the context of the research. Research shows that the use of AI in economic terms increases productivity, facilitates innovation, and adapts the labour market to the digital age, while the challenges of AI integration relate to privacy and data security, labour market disruptions, and ethical issues related to machine decision-making. Therefore, despite the significant challenges, with a wise and proactive approach, the transition to the era of artificial intelligence can be a major driver of economic optimization and social progress.